Surplus majority government a comparative study of Italy and Finland - Jungar, Ann-Cathrine 1962- (Uppsala Univ. Library, 2000)
Abstract.
Zugl.: Uppsala, Univ., Diss., 2000
Keywords: Geschichte 1981-1995; Geschichte 1995; Geschichte 1981-1991; hallitukset; hallitusmuodot; koalitiot; parlamentarismi; puolueet; Parteiensystem; Politische Theorie; Koalition; Italia; Suomi; Finnland; Italien; Hochschulschrift